an examination of the macro-economic influence on nominal and real interest rate spreads in the Caribbean - Birchwood, Anthony ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2004)
Investigates the type of macroeconomic influences that may have helped to account for differences in interest rate spreads in the region, for the period 1991 to 2002.